Paraneoplastic eczematous eruption associated with Hodgkin's lymphoma. Issue 4 (2nd October 2019) - Asad, Usman; Austin, Brett; Sturgeon, Ashley; Stetson, Cloyce
Abstract: Hodgkin's disease (HD) is a common malignant lymphoma that classically presents with painless lymphadenopathy, weight loss, nocturnal sweats, fever, and generalized pruritus. Unlike other lymphoproliferative disorders, cutaneous involvement is uncommon with HD. Diffuse hyperpigmentation, prurigo nodularis, acquired ichthyosis, erythema nodosum, mycosis fungoides, herpes zoster, and vasculitis have all been described as nonspecific or paraneoplastic manifestations of HD. A small set of cases of adult new-onset recalcitrant eczema has recently been described as a nonspecific cutaneous manifestation of HD. In agreement with these reports, we present a case of a 28-year-old woman who initially presented with persistent lymphadenopathy and a pruritic eczematous dermatitis that preceded the diagnosis of HD.